Cyanobacterial NOS expression improves nitrogen use efficiency, nitrogen-deficiency tolerance and yield in Arabidopsis. (June 2021) - Del Castello, Fiorella; Foresi, Noelia; Nejamkin, Andrés; Lindermayr, Christian; Buegger, Franz; Lamattina, Lorenzo; Correa-Aragunde, Natalia
Highlights: The nitric oxide (NO) synthase from Synechococcus PCC 7335 (SyNOS) produces citrulline and NO from Arginine, but also can oxidize NO to nitrate. The heterologous SyNOS expression in Arabidopsis affects N metabolism improving NUE and seed production under high and low N conditions. SyNOS lines have higher tolerance to N-deficiency preventing chlorophyll degradation and diminishing anthocyanin production. SyNOS expression in plants enhance the expression of genes involved in N assimilation and increase N remobilization to seed filling. Abstract: Developing strategies to improve nitrogen (N) use efficiency (NUE) in plants is a challenge to reduce environmental problems linked to over‐fertilization. The nitric oxide synthase (NOS) enzyme from the cyanobacteria Synechococcus PCC 7335 (SyNOS) has been recently identified and characterized. SyNOS catalyzes the conversion of arginine to citrulline and nitric oxide (NO), and then approximately 75 % of the produced NO is rapidly oxidized to nitrate by an unusual globin domain in the N-terminus of the enzyme. In this study, we assessed whether SyNOS expression in plants affects N metabolism, NUE and yield. Our results showed that SyNOS-expressing transgenic Arabidopsis plants have greater primary shoot length and shoot branching when grown under N-deficient conditions and higher seed production both under N-sufficient and N-deficient conditions. Moreover, transgenic plants showed significantly increased NUE in both N conditions. Although the uptake of N was not modified in the SyNOS lines, they showed an increase in the assimilation/remobilization of N under conditions of low N availability. In addition, SyNOS lines have greater N-deficiency tolerance compared to control plants. Our results support that SyNOS expression generates a positive effect on N metabolism and seed production in Arabidopsis, and it might be envisaged as a strategy to improve productivity in crops under adverse N environments.